BQ-Chem: A Quantum Software Program for Chemistry Simulation Based on the Full Quantum Eigensolver Algorithm. (7th December 2022) - Li, Hang; Gao, Pan; Zhang, Jiang; Liu, Zhiyuan; Wei, Hai; Wen, Kai; Wei, Shijie; Long, Gui-Lu
Abstract : We describe a quantum chemistry simulation software program BQ-Chem, which can calculate the low-energy spectrum and potential energy surface of molecules on a quantum computer. BQ-Chem is based on the full quantum eigensolver (FQE), which is implemented with a quantum gradient descent algorithm. Benefiting from FQE, BQ-Chem can perform all the calculations on a quantum computer. Compared with the classical optimization methods which encounter the optimization difficulty of high-dimensional and multivariable functions in dealing with multielectron orbitals of macromolecules, FQE provides an exponential speedup. FQE works fully on a quantum computer; thus, BQ-Chem can be smoothly transited to future large-scale quantum computers.